Effects of Colchicine Concentration Level and Soaking Period to Induce Polyploid Mutation on Five Forage Sorghum (Sorghum bicolor L. Moench) Cultivars - Poosamart, Worames; Siniri, Naris; Simia, Sakunkan (Journal of Mahanakorn Veterinary Medicine, 2018)
This study was to investigate the effect of the colchicine concentration level, soaking period, and five forage sorghum (Sorghum bicolor L. Moench) cultivars on the occurrence of polyploidy. The 4x5x5 factorial arrangement in Completely Randomized Design (CRD) was employed through 3 factors: 4 colchicine concentrations level (0, 0.1, 0.2 and 0.3%), 5 soaking periods (0, 12, 24, 48 and 72 hours) and 5 forage sorghum cultivars (Cowley, Rio, IS23585, Keller and Wray). The results revealed that there was a significant difference among colchicine concentrations level, soaking periods, and sorghum cultivars; when colchicine concentration level increased and soaking period increased, the survival rate of sorghum decreased variously but occurrence of polyploidy chromosome increased differently among cultivars. Cowley sorghum soaking in the colchicine concentration at 0.1% for both 48 and 72 hours had mutation polyploidy 3.3 and 2.3 % respectively. Cowley sorghum soaking in the colchicine concentration at 0.2% for both 24 and 48 hours had mutation polyploidy 4.1 and 3.2 % respectively and soaking in the colchicine concentration at 0.3% for 24 hours had mutation polyploidy 4.0%. While, Rio sorghum soaking in the colchicine concentration at 0.1% for 48 hours had mutation polyploidy 2.2 % and soaking in the colchicine concentration at 0.2 % for 24 and 48 hours had mutation polyploidy 5.2 and 2.6 % respectively. For IS23585, Keller and Wray sorghum cultivars weren’t significant different effect of the colchicine concentration level and soaking period. However, considering the frequency of the occurrence of seedling having the polyploidy chromosome soaking in the colchicine concentration of 0.2% for 48 hours was the most appropriate concentration and period or duration for the occurrence of the plant with the polyploidy chromosome.